An Investigation of the Behaviour and Biology of the Citrus Mussel Scale, Lepidosaphes Beckii (Newm.) - Hulley, P. E. (University of Ghana, 1960)
The citrus industry is subject to a number of serious insect pests. Of these, the most important is a sedentary group known as the...Armoured Scale Insects (Diaspididae). Ebeling (1950) states that they are of greater economic importance to the industry than all the other pests put together. A great deal has been published on various aspects of the biology, ecology and control of the Diaspididae, much of the work appearing in the books of Quayle (193S), Ebeling (1950) and Bodenheimer (l9 5 l)≫ It is very noticeable, however, that the study of the active larvae, or ’’ crawlers” , of these insects has been relatively neglected* This lack of work on crawlers is surprising, since they are the only distributive stage in the life cycle of the species. The adult male is also free - livin g during its brief life span, but takes no part in the actual distribution of the species. I t is the position of the female Scale Insect which is important in determining the further spread of the species, since this is the point from which subsequent crawlers will start out on their wanderings. The stage in the life cycle responsible for the position of the female is, of course, the crawler. The crawler is also responsible for the parallel distribution of the male Scales, so that the female can be fertilised . The r&le oj. tne adult male is confined to the maintenance of the gene flow* From an economic point of view it seems desirable that a complete study be made of the biology of this distributive stage of these important pests. Information on factors influencing the hatching (or birth of ovoviviparous species), and emergence from beneath the scale-covering of the female, would be useful.
Thesis (MSc) - University of Ghana, 1960
Keywords: Insect Pests; Citrus; Insect Lifespan; Citrus Mussel Scale